Who cheats more? Gender and academic dishonesty among Malaysian undergraduates in English medium classrooms / Zachariah Aidin Druckman ... [et al.] - Druckman, Zachariah Aidin; Rahmat, Noor Hanim; Ahmad Kamil, Maisarah; Amir Johan, Syafiqah Johan (Akademi Pengajian Bahasa, 2019)
Academic dishonesty (AD) is a significant problem in tertiary institutions worldwide, including Malaysia. The self-presentation theory suggests that AD may be committed in order to make or preserve a favourable image to others. Past studies have made the generalisation that male students commit more AD compared to female students, however, few studies have looked into the actual differences in the instances and methods of AD across genders. Hence, the authors conducted a questionnaire to examine whether gender is a significant indicator of AD and whether there are differences in the types of AD committed. The results show that male students outnumbered their female counterparts in all categories except crediting absent partners in group tasks. Findings of this study suggest that assessments should be designed to reward the quality, not quantity, of output.